Peningkatan Hasil Belajar Siswamenggunakan Media Pembelajaran 3D Di Kelas II SDN Mandalajaya - Denna Permana Kusuma; Winarti Dwi Febriani; Hatma Heris Mahendra (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This research is motivated by the low student learning outcomes in mathematics learning on geometry material in the 2ndSDN Mandalajaya. This study aims to identify and analyze the planning, implementation, and improvement of mathematics learning outcomes using media 3D. The method used in this study was Classroom Action Research (PTK) with 19 students as research objects. The PTK model used is the CAR research method according to Kemmis and Mc. Taggart which consists of planning, action, observation, and reflection in each cycle. The discussion of this study uses media 3D in the process of learning mathematics with geometry material which is tested at the end of each cycle. Data collection techniques in this study by means of observation, tests, and documentation. And the data analysis used is descriptive data analysis. The results of the study concluded that student learning outcomes in mathematics learning using media 3D in the 2nd SDN Mandalajaya were able to improve student learning outcomes. This increase before using 3D media (pre-action) obtained an average score of 63.52 with a completeness percentage of 36.86 in the "low" category. After using media 3D in cycle I, an average score of 73.68 was obtained with a completeness percentage of 47.36 %. category "good" Then in cycle II obtained an average value of 80.52 with a percentage of 76.68% in the "good" category. So that the use of media 3D is very well applied in classroom learning.